Recurrent de novo mutations in CLDN5 induce an anion-selective blood-brain barrier and alternating hemiplegia - Campbell, Matthew (My University, 2022)
Claudin-5 is the most enriched tight junction protein at the blood–brain barrier. Perturbations in its levels of expression have been observed across numerous neurological and neuropsychiatric conditions; however, pathogenic variants in the coding sequence of the gene have never been reported previously. Here, we report the identification of a novel de novo mutation (c.178G>A) in the CLDN5 gene in two unrelated cases of alternating hemiplegia with microcephaly. This mutation (G60R) lies within the first extracellular loop of claudin-5 and based on protein modelling and sequence alignment, we predicted it would modify claudin-5 to become an anion-selective junctional component as opposed to a purely barrier-forming protein. Generation of stably transfected cell lines expressing wild-type or G60R claudin-5 showed that the tight junctions could still form in the presence of the G60R mutation but that the barrier against small molecules was clearly attenuated and displayed higher Cl− ion permeability and lower Na+ permeability. While this study strongly suggests that CLDN5 associated alternating hemiplegia is a channelopathy, it is also the first study to identify the conversion of the blood–brain barrier to an anion-selective channel mediated by a dominant acting variant in CLDN5.
PUBLISHED
cited By 2
Keywords: blood–brain barrier; claudin-5; tight junction; alternating hemiplegia; channelopathy